½M Coffee: A Saudi Specialty Coffee Phenomenon - Kurniawan Arif Maspul; Syamsu Hidayat (Pubmedia Social Sciences and Humanities, 2026)
This study examines ½M Coffee as a distinctive phenomenon at the intersection of Saudi Arabia's Vision 2030 transformation, geopolitical consumer activism, and the evolution of cultural diplomacy. While existing literature addresses specialty coffee markets or soft power separately, this research reveals how a single domestic brand has become an unexpected vehicle for national identity renegotiation, quiet resistance, and global image-making. Through qualitative case study methodology and systematic document analysis—including industry reports, UNESCO inscriptions, FAO technical documents, and regional media—this investigation traces ½M's trajectory from local start-up to transnational symbol. The findings demonstrate three novel contributions: First, ½M's success is not merely commercial but fundamentally political, capitalising on boycott dynamics following the Gaza war to position itself as an ethical alternative to Western chains. Second, the brand exemplifies what this study terms "algorithmic authenticity"—the deliberate crafting of Instagrammable heritage that simultaneously performs tradition and hyper-modernity for digital consumption. Third, ½M functions as an unofficial instrument of Saudi soft power, carrying cultural narratives across borders through every exported tumbler and London flagship visit. This analysis challenges conventional understandings of coffee as an apolitical commodity, arguing instead that in contemporary Muslim-majority markets, specialty coffee has become a terrain where economic ambition, cultural assertion, and geopolitical stance converge. The study concludes by offering policy-relevant insights for sustainable, inclusive coffee diplomacy that balances global reach with authentic heritage preservation.